Value chain mapping and marketing efficiency of cowpea farmers in Capricorn and Waterberg Districts of Limpopo Province, South Africa - Masegela, Christina Magosea (My University, 2019)
Agriculture plays a significant role also serves as a critical economic sector in Limpopo province in terms of its contribution to the economy, and the number of employment opportunities it produces within local communities. The majority of people involved in agricultural practices are emerging farmers and smallholder/small scale farmers. These farmers try to earn a living from the production of livestock, broilers, fruits & vegetables, and cereals. Cowpea is a drought-tolerant legume that also serves as a staple food for the majority of Africans alongside maize and other typical staple foods consumed by most Africans. The crop is regarded as a key protein source for urban and rural poor, and plays an important role as a cash crop. Despite several nutritional benefits, economic importance and welfare enhancing potential of cowpea, farmers still do not have sufficient information on knowledge about the value that can be added to their cowpea production also the potential and competitiveness of this traditional leafy vegetable. The aim of the study was to map the value chain and determine the marketing efficiency of smallholder cowpea farmers in Capricorn and Waterberg districts of Limpopo province. The specific objectives were to: identify and describe socioeconomic characteristics of smallholder cowpea farmers in Capricorn and Waterberg districts of Limpopo province, identify and define the participants along the cowpea value chain and identify marketing constraints among smallholder cowpea farmers. Structured questionnaire was used to collect data from 80 smallholder cowpea farmers in Ga-Molepo of Capricorn district and Bela-Bela of Waterberg district using purposive sampling technique. Value chain mapping, descriptive statistics and binary logistic regression model were used in addressing the objectives. In identifying and defining the participants along the cowpea value chain, a value chain map was constructed to show the different stages cowpea goes through before reaching the final consumer. Two null hypotheses were formulated. The first hypothesis that stated smallholder cowpea farmers were inefficient in marketing cowpea was rejected. Marketing efficiency measure used to determine each farmer’s marketing efficiency revealed that 66% of smallholder cowpea farmers were efficient. The determinants of marketing efficiency were examined using binary logistic regression model. The second hypothesis stated that socioeconomic characteristics of smallholder cowpea farmers have no effect on the marketing efficiency. The v hypothesis was also rejected based on binary logistic results that revealed that age, household size, years in schooling, years in farming cowpea, income generated from selling cowpea, quantities of cowpea sold and occupation of the farmers were found to be significant in determining marketing efficiency of smallholder cowpea farmers. Pests, lack of access to formal markets and lack of information on how to process cowpea were major constraints farmers were faced with. It was recommended that value chain analysts, policy makers and extension workers together with other stakeholders assist in ensuring that food value chain relationships are established so that market opportunities can be created for smallholder cowpea farmers. In addition, farmer schools need to be introduced in rural areas were agricultural practices are dominant. At these schools, farmers can be taught about basic knowledge relating to agricultural production. Training should also be given to farmers on adopting technology as it can potentially assist in making production more efficient.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2019
Keywords: Value chain mapping; Cowpea; Small-scale farmers; Agricultural marketing; Cowpea -- Marketing; Cowpea -- South Africa -- Limpopo; Farmers -- South Africa -- Limpopo